Improving carbohydrate production of Chlorella sorokiniana NIES‐2168 through semi‐continuous process coupled with mixotrophic cultivation. Issue 8 (24th June 2016) - Wang, Yue; Chiu, Sheng‐Yi; Ho, Shih‐Hsin; Liu, Zhuo; Hasunuma, Tomohisa; Chang, Ting‐Ting; Chang, Kuan‐Fu; Chang, Jo‐Shu; Ren, Nan‐Qi; Kondo, Akihiko
Abstract: Biofuels from microalgae is now a hot issue of great potential. However, achieving high starch productivity with photoautotrophic microalgae is still challenging. A feasible approach to enhance the growth and target product of microalgae is to conduct mixotrophic cultivation. The appropriate acetate addition combined with CO2 supply as dual carbon sources (i.e., mixotrophic cultivation) could enhance the cell growth of some microalgae species, but the effect of acetate‐mediated mixotrophic culture mode on carbohydrate accumulation in microalgae remains unclear. Moreover, there is still lack of the information concerning how to increase the productivity of carbohydrates from microalgae under acetate‐amended mixotrophic cultivation and how to optimize the engineering strategies to achieve the goal. This study was undertaken to develop an optimal acetate‐contained mixotrophic cultivation system coupled with effective operation strategies to markedly improve the carbohydrate productivity of Chlorella sorokiniana NIES‐2168. The optimal carbohydrate productivity of 695 mg/L/d was obtained, which is the highest value ever reported. The monosaccharide in the accumulated carbohydrates is mainly glucose (i.e., 85–90%), which is very suitable for bio‐alcohols fermentation. Hence, by applying the optimal process developed in this study, C. sorokiniana NIES‐2168 has a high potential to serve as a feedstock for subsequent biofuels conversion. Abstract : Acetate can increase the biomass production and trigger the starch biosynthesis during microalgal mixotrophic cultivation. In this study, the authors develop an optimal acetate‐contained mixotrophic cultivation system coupled with effective operation strategies to markedly improve the carbohydrate productivity of Chlorella sorokiniana NIES‐2168. Thus Chlorella sorokiniana NIES‐2168 has a high potential to serve as a feedstock for subsequent biofuels conversion.